The Sustainable Development Goals and the application of International Law: the case of the Grand Ethiopian Renaissance Dam - Cardona-Vallès, Mariona; Preller-Bórquez, Sebastián (Iberoamerican Journal of Development Studies, 2022)
In this article, it is examined the role that the sustainable development goals may play in the harmonious interpretation and systemic integration of international law. The backdrop to evaluate this hypothesis is the conflict between Ethiopia, Sudan, and Egypt, which arose out of the construction of the Grand Ethiopian Renaissance Dam. Considering the wide range of interests at stake and the different special regimes of international law that may apply to the settlement of this controversy, in this paper, it is argued that a perspective grounded in the notion of sustainable development may contribute to ease the dialogue between the parties and ensure compliance of their reciprocal international obligations. Focusing on the harmonious interpretation of the different regimes converging in this conflict, it is proposed that the 2030 Agenda for Sustainable Development can operate as a kaleidoscopic lens to harmonize international obligations to a certain extent.
Keywords: Grand Ethiopian Renaissance Dam; sustainable development; interpretation; systemic integration; fragmentation; conflict of norms